Intergovernmental relations in the local sphere of government in South Africa with specific reference to the City of Tshwane Metropolitan Municipality - Kuye, Jerry O. (University of Pretoria, 2013)
Thesis (PhD (Public Affairs))--University of Pretoria, 2006.